Faktor Intention to Stay pada Karyawan dalam Lingkungan Kerja: Pendekatan Systematic Literature Review - Nurhalizah, Hayyumu Farina; Rizki Sridadi, Ahmad; Eliyana, Anis (Journal of Management and Bussines (JOMB), 2024)
This study aims to explore the factors that contribute to employee intention to stay in a work environment. The method used in this study is a systematic literature review of PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) using articles from the Scopus database from 2018 to 2023. The results of the study indicate that the factors that influence employee intention to stay based on the literature review conducted by author 1 are talent development, work intensification, cultural competence, aspects (psychological, rational, and fundamental), perceived organizational factors, spirituality in the workplace, promotion, job satisfaction, stress, work frequency, training, mentoring, work environment, distributive justice, paternalistic leadership, trust in management, clarity of goals, work family conflict, rational job creation, HR practices (recruitment, training, performance appraisal, rewards, career opportunities), organizational practices, perception of calling, learning opportunities, and employee value proposition (EVP). Keywords: Intention To Stay, Workplace, Systematic Literature Review